Effect of addition of adjuvants on physical and chemical characteristics of Bt bioinsecticide mixture - Santos, Cicero Antônio Mariano dos [UNESP] (2019)
Bacillus thuringiensis (Bt) is the main bacterium used in the formulation of bioinsecticides because it produces toxins and spores that are toxic to several orders of insects. The efficacy of Bt bioinsecticide is influenced by the quality of its application. The association with other crop protection products, such as adjuvants, can affect the physical and chemical parameters of the mixture. This study evaluated the physical and chemical parameters, volume median diameter (VMD), uniformity coefficient of droplets (SPAN), percentage of volume in drift droplets (%V <100 µm), contact angle, surface tension, potential of hydrogen (pH) and electrical conductivity (E.C.) of Bt bioinsecticides in concentrated suspension (SC), and wettable powder (WP) formulations associated with adjuvants. The largest droplet diameter and smallest values of drift droplets were found in the WP formulation with lower drift potential. The addition of mineral oil and surfactant to the mixtures of bioinsecticide reduced contact angle values and surface tension of the droplets, resulting in greater spreading of droplets in leaves. The addition of lecithin and propionic-acid-based adjuvants lowered the pH in both formulations. The adjuvants used in this study affected the physical and chemical characteristics of the mixtures, improving or impairing the quality of Bt bioinsecticide applications.